(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This article analyzes how the BRICS countries and Qatar used sporting mega-events as a discourse to expand their political influence. To this end, the article discusses (a) the public sphere and its interfaces in sports and (b) the 2010 to 2022 World Cups as examples of Soft Power, Sportswashing, and Sports Diplomacy. As an analytical structure, we will make an interface between the studies that discussed the role of the Western media during the events and FIFA’s 3 S’s. The central argument resides in FIFA’s 3 S’srole during the World Cup cycle in countries of the Global South and the existence of a FIFA modus operandi in the last four World Cups.